Cementless bipolar hemiarthroplasty in femoral neck fractures in elderly - Marya, SKS (Medknow Publications, 2011)
BACKGROUND: Cemented hip arthroplasty is an established treatment for femoral neck fracture in the mobile elderly. Cement pressurization raises intramedullary pressure and may lead to fat embolization, resulting in fatal bone cement implantation syndrome, particularly in patients with multiple comorbidities. The cementless stem technique may reduce this mortality risk but it is technically demanding and needs precise planning and execution. We report the perioperative mortality and morbidity of cementless bipolar hemiarthroplasty in a series of mobile elderly patients (age >70 years) with femoral neck fractures. MATERIALS AND METHODS: Twenty-nine elderly patients with mean age of 83 years (range:71-102 years) with femoral neck fractures (23 neck of femur and 6 intertrochanteric) were operated over a 2-year period (Nov 2005–Oct 2007). All were treated with cementless bipolar hemiarthroplasty. Clinical and radiological follow-up was done at 3 months, 6 months, 12 months, and then yearly. RESULTS: The average follow-up was 36 months (range 26-49 months). The average duration of surgery and blood loss was 28 min from skin to skin (range, 20–50 min) and 260 ml (range, 95–535 ml), respectively. Average blood transfusion was 1.4 units (range, 0 to 4 units) Mean duration of hospital stay was 11.9 days (7–26 days). We had no perioperative mortality or serious morbidity. We lost two patients to follow-up after 12 months, while three others died due to medical conditions (10–16 months post surgery). Twenty-four patients were followed to final follow-up (average 36 months; range: 26–49 months). All were ambulatory and had painless hips; the mean Harris hip score was 85 (range: 69–96). CONCLUSION: Cementless bipolar hemiarthroplasty for femoral neck fractures in the very elderly permits early return to premorbid life and is not associated with any untoward cardiac event in the perioperative period. It can be considered a treatment option in this select group.